Frugivory in cotingas of the Atlantic Forest of southeast Brazil - Pizo, Marco A. [UNESP] (2002)
In this paper we present a list of plant species whose fruits are eaten by eight cotinga species (Carpornis cucullatus, C. melanocephalus, Laniisoma elegans, Lipaugus lanioides, Oxyruncus cristatus, Phibalura flavirostris, Procnias nudicollis, and Pyroderus scutatus) at Parque Estadual Intervales (PEI), an Atlantic Forest reserve in southeast Brazil. Besides providing a list of fruits eaten by cotingas, our goal is to allow insights into fruit use by these birds whose ecology is poorly known. From 1990 to 2001 four sites located within PEI were regularly visited. These sites form an altitudinal gradient (70-800 m a.s.l.) and also a gradient of forest disturbance (second-growth to old-growth vegetation). Feeding records were made along several trails and dirt roads that crossed the study sites. Cotingas ate a variety of fruits (99 species in 34 families) that ranged from small (< 5 mm diameter) to large (up to 37 mm) and included some non-ornithochorous ones. With the exception of P. nudicollis, cotingas exploited not only fruits typical of the forest interior but also fruits of secondary vegetation, suggesting that concerning fruit exploitation early successional vegetation does not represent a barrier for the survival of these cotingas.